Hydrauliczne Obliczenie Studni o Drenach Promienistych Zakładanych w Pobliżu Rzeki - Kordas, B. (Engineering Transactions, 1963)
The source and sink method is used for the purpose of hydraulic computation of a well with radial drains in the neighbourhood of a river.To solve the problem the following is assumed: a) the soil is homogeneous and isotropic, b) the motion of ground water constitutes a steady-state potential flow subjected to the Darcy law,c) the flow rate in a drain qi is constant along the entire length of the drain. The first part of the paper contains an analysis of a well with radial drains in a basin of artesian waters in contact with a river. General Eq. (3.3) is derived for the depression function satisfying the boundary conditions (2.2) and (2.3). By performing an operation analogous to that used by POLUBARINOVA-KOTCHINA, [12], the canonial set of linear Eq. (4.1) is obtained from (3.3). Solving this set of equations we obtain equations determining the flow rate in a drain qi. The total flow rate is determined by (4.2). In the second part of the paper the object of the analysis is a well with radial drains in a basin of ground waters with free surface communicating with a river. General equation for the velocity potential is given, (5.3), which can be used to determine the flow rate of a drain qi (the way in which. this equation is used to obtain qt is similar to that of the previous case). General equation of the free surface of ground water (5.6) is derived. This can be made use of to find the depression in the collector well.